Faktor - Faktor yang Mempengaruhi Pertimbangan Tingkat Materialitas Dalam Pengauditan Laporan Keuangan - cahyati, dinda; Murni, Yetty; Nelyumna, Nelyumna; Azizah, Widyaningsih (Fakultas Ekonomi dan Bisnis Universitas Pancasila, 2025)
The study aims to test and analyze the influence of auditor profesionalisme, auditor experience, auditor competence, the ethics of the auditor profession, audit risk, and auditor independence on the level of materiality in financial statements at the public accounting office in Jakarta Selatan. The population used in this study an auditor-auditor who works in the public accounting office in the Jakarta Selatan region. The sample in this study was determined using purposive sampling, and based on the method obtained 14 public accounting office in Jakarta Selatan. This research uses primary data obtained through a questionnaire. The analysis method used in this study SPSS Version 30. The result of this study indicate that professionalism greatly influences the consideration of materiality levels in financial statements audits.